The Impact of Social Media Advertisements on Purchase Intentions: An Empirical Study on Food Industry in Jordan - Alhaddad, Shafig; Ayesh, Osama; A lHassan, Salam; Abu Talib, Jawa; Abu Talib, Farah; Al Otaibi, Layan (Jordan Journal of Business Administration, 2021)
The purpose of this study is to discover how social media advertisement factors (Informativeness, Entertainment, Credibility and Perceived Value) have an impact on Jordanian customers’ purchase intentions in food industry. Three social media channels have been considered, as they are the top channels businesses intend to use nowadays for publishing their advertisements. Facebook, Instagram and YouTube channels are the studied online channels in this study. Multiple regression was used to analyze the data, as well as the SPSS to test the hypotheses. 211 received a survey that was constructed using Google Forms and distributed using online channels, such as WhatsApp, Facebook and Twitter, noting that the sample of the study was a convenience sample, as the researchers focused on adult social media users in general. The scale used in the survey was developed by Dao et al. (2014). The results indicated that the studied factors have an impact on Jordanian customers’ purchase intentions in food industry, but at different levels. Perceived value is considered as the most influential factor affecting the purchase intention, while credibility is considered as the least influential factor helping in changing customers' purchase intention.